Multilingualism in the FET band schools of Polokwane area, a myth or a reality - Ntsoane, Mogodi (University of Limpopo (Turfloop Campus), 2008)
Language prejudice is of two types: positive and negative. Negative prejudice is image effacing. It is characterized by negative evaluation of one’s own language or speech patterns and a preference for someone else’s. An example of this kind of self- -denigration is the case of David Christiaan, the Nama Chief in Namibia, who, in response to the Dutch missionaries’ attempt to open schools that would conduct their teaching using Nama as a medium of instruction, is reported to have shouted, “Only Dutch, Dutch only! I despise myself and I want to hide in the bush when I am talking my Hottentot language” (Vedder, 1981: 275 as quoted in Ohly, 1992:65. In Ambrose, et al (eds.) undated: 15).
Thesis (M.ED.) --University of Limpopo, 2008
Keywords: Multilingualism; Further Education and Training band schools; 370.117; Multilingualism -- South Africa; Education, Higher -- South Africa